Contested Terrain Reconceptualising Security in the Pacific Contested Terrain - Ratuva, Steven (ANU Press, 2019)
Contested Terrain provides a cutting-edge, comprehensive and innovative approach to critically analysing the multidimensional and contested nature of security narratives, justified by different ideological, political, cultural and economic rationales. This is important in a complex and ever-changing situation involving a dynamic interplay between local, regional and global factors. Security narratives are constructed in multiple ways and are used to frame our responses to the challenges and threats to our sense of safety, wellbeing, identity and survival but how the narratives are constructed is a matter of intellectual and political contestation. Using three case studies from the Pacific (Fiji, Tonga and Solomon Islands), Contested Terrain shows the different security challenges facing each country, which result from their unique historical, political and socio-cultural circumstances. Contrary to the view that the Pacific is a generic entity with common security issues, this book argues for more localised and nuanced approaches to security framing and analysis.